Creative Titles: Audiovisual Experimentation and Self-Reflexivity in Italian Industrial Films of the Economic Miracle and After. Issue 2 (23rd January 2015) - Cecchi, Alessandro
Abstract : After discussing the relationship of title sequences to Genette's concept of the paratext, along with the definition of the film as text, this article provides an historical contextualisation of a sub-genre of the Italian industrial film characterised by musical and audiovisual experimentation, which arose in the years of the economic miracle (1958-63), flourished throughout the 1960s and came to an end in the early 1970s. The article goes on to analyse some significant examples, exploring three main issues: the relationship of title sequences to a film's structure, their semantic and rhetorical strategies with particular attention to self-reflexivity, and finally their impact relative to the audience's experience.